Discovery of Bergamotanes against Hepatic Ischemia–Reperfusion Injury Based on DeepSAT Technology from Paraconiothyrium sp. H–B - Xinye Huang (22365057) (2025)
Hepatic ischemia–reperfusion injury (HIRI) is a common and inevitable complication of liver surgery that induces severe hepatic functional impairment and can trigger multiple organ dysfunction syndrome. From the rice culture of Paraconiothyrium sp. H–B collected from Hypericum wilsonii N. Robson, 11 novel bergamotane-type sesquiterpenoids, paramotanes A-K (1–11), along with three known congeners, were obtained by the guidance of the DeepSAT system (a neural network-based tool for HSQC spectrum analysis). The structures and configurations of these compounds were confirmed via spectroscopic analysis, single-crystal X-ray diffraction, and electronic circular dichroism (ECD) calculations. Notably, compound 1 is the first reported 10-nor-bergamotane sesquiterpenoid. The pharmacodynamics assays demonstrated that compound 12 exhibits hepatoprotective effects and can ameliorate liver function in HIRI mice, positioning it as a promising leading compound for developing novel hepatoprotective agents for the clinical management of HIRI.